IDEAS OF FOUR-FERMION OPERATORS IN HADRON PHYSICS - Ji, Chueng-Ryong; Bakker, Bernard L. G.; Choi, Ho-Meoyng; Suzuki, Alfredo T. [UNESP]; Broniowski, W.; Praszalowicz, M. (J C B Mohr (paul Siebeck), 2013)
Four-fermion operators have been utilized in the past to link the quark-exchange processes in the interaction of hadrons with the effective meson-exchange amplitudes. In this paper, we apply the similar idea of Fierz rearrangement to the electromagnetic processes and focus on the electromagnetic form factors of nucleon and electron. We explain the motivation of using four-fermion operators and discuss the advantage of this method in computing electromagnetic processes.